Relationships between physical activity, body image, BMI, depression and anxiety in Chinese college students during the COVID-19 pandemic - Bing Han; Guoli Du; Yashu Yang; Jiping Chen; Guoxiao Sun (BMC, 2023)
Abstract Background Both depression and anxiety are worldwide burden that is not being abated with our current knowledge and treatment of the condition. Numerous clinical trials have supported that physical activity (PA) can reduce the depression and anxiety in adolescents, but little is known about its mechanism of action. Therefore, the study objectives were to explore the potential relationship between physical activity and depression and anxiety from the perspective of body image and body mass index (BMI), and to provide an important reference for future self-esteem education and health promotion intervention. Methods The participants in this study were 251 Chinese college students between 17 and 22 years old. Participants completed the International Physical Activity Questionnaire-Short Form (IPAQ-SF), the Body Image Questionnaire (BIQ), the Self-rating Depression Scale (SDS) and the Self-rating Anxiety Scale (SAS). A descriptive and correlational approach was used, using the PROCESS macro for Statistical Package for the Social Sciences (SPSS). Results (1) Physical activity was significantly negatively correlated with both depression and anxiety (t = -0.216, p < 0.001; t = -0.184, p < 0.01). (2) Body image had a significant moderating effect on the relationship between physical activity and anxiety among college students, but there was no moderating effect between depression and physical activity. BMI has no moderating effect on the two interrelationships. Conclusion There is only body image that moderates the relationship between anxiety and physical activity.